Symposium policy note 1: Enabling farmers to lead food system transformation and resilience in Egypt - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
Agricultural and food policies will play an important role in making Egypt’s food system fit for future challenges, including resilience to shocks, such as the ongoing COVID-19 pandemic. This brief highlights the importance of enabling farmers so that they can contribute significantly to a broader transformation and to resilience of Egypt’s food system and rural economy. Five areas of action are highlighted: Invest in a renewed system of agricultural extension services, with an emphasis on new technologies and production systems and on nontraditional crops. Ease rigidities for farmers and increase the market orientation of the agriculture sector, including markets for fertilizer and staple crops. Revisit the current irrigation management system to allow for the adoption of new irrigation technologies and increased efficiency of water usage. Support the development of agro-processing value chains where there are missing markets or market frictions in order to achieve a sustainable and nutrition-sensitive food system. Coordinate agricultural policy with policies of other government ministries to support rural transformation and employment opportunities off the farm.